Adaptation and validation of the Physical Activity Questionnaire for Adolescents (PAQ-A) among Polish adolescents: cross-sectional study. Issue 11 (18th November 2019) - Wyszyńska, Justyna; Matłosz, Piotr; Podgórska-Bednarz, Justyna; Herbert, Jarosław; Przednowek, Krzysztof; Baran, Joanna; Dereń, Katarzyna; Mazur, Artur
Abstract : Objective: The lack of a widely accepted questionnaire used to assess the physical activity (PA) of adolescents in the Polish language creates a need to introduce such a valid, reliable, inexpensive and quick tool for assessment. This study was designed to culturally adapt and validate the Physical Activity Questionnaires for Adolescents (PAQ-A) in the Polish language. Design: Cross-sectional study. Participants and outcome measures: Cultural adaptation of the Polish version of the PAQ-A was performed following the standardised questionnaires cultural adaptation process. In a sample of 78 adolescents aged 14–19 years, the PAQ-A test–retest was administered within a 1-week interval. Reliability was analysed by the intraclass correlation coefficient (ICC) and internal consistency with Cronbach's α. Participants completed the PAQ-A, and wore an accelerometer for 7 consecutive days. The PAQ-A was compared with PA parameters obtained using the accelerometer. Results: Test–retest reliability showed ICC=0.97 for the total score of PAQ-A. Internal consistency was excellent (α=0.93). The PAQ-A was very strongly correlated with steps per day (r=0.94) and with moderate-to-vigorous PA (r=0.81) assessed by the accelerometer. Conclusions: The Polish version of the PAQ-A is a valuable tool to estimate general levels of PA among adolescents from 14 to 19 years old.